Immunohistochemical evaluation is not prognostic for recurrence in fully staged high-risk endometrial cancer. Issue 3 (1st April 2002) - Fanning, J; Brown, S; Phibbs, G; Kramer, T; Zaher, A
Abstract : Abstract: Fanning J, Brown S, Phibbs G, Kramer T, Zaher A. Immunohistochemical evaluation is not prognostic for recurrence in fully staged high-risk endometrial cancer. The objective of this study was to determine the prognostic significance of common immunohistochemical pathologic risk factors in fully staged high-risk endometrial cancers. Sixty-two of 265 consecutive endometrioid adenocarcinomas were considered high risk for recurrence because of deep myometrial invasion and poor differentiation (stage IC, G3), cervical metastasis (stage II), ovarian metastasis (stage IIIA) or lymph node metastasis (stage IIIC). All patients underwent complete surgical staging with bilateral pelvic and aortic lymphadenectomy. Expression of estrogen receptors, progesterone receptors, p53, HER-2/neu, c-myc, bcl-2, FVIII, and Ki-67 were analyzed by immunohistochemistry using commercially available monoclonal antibodies. A general linear model multiple regression analysis was used to determine if any of the immunostains, along with grade or stage, were predictors of recurrence. Mean age was 68 years and mean weight 188 pounds. Sixty-eight percent of patients had associated medical illness. The majority of tumors were poorly differentiated (44%) and were stage IIIC (29%). Mean follow-up was 4.3 years. Fourteen patients (22%) developed tumor recurrence. Using multiple regression analysis, none of the immunostains were predictive for recurrence ( P = 0.19-.96). Only stage and grade were predictive of tumor recurrence ( P = 0.04, .02). We conclude that in completely staged high risk endometrial cancer, commonly used immunohistochemical risk factors are not predictive for recurrence.